A fused-ring non-fullerene acceptor based on a benzo[1, 2-b:4, 5-b′]dithiophene central core with a thieno[3, 2-b]thiophene side-chain for highly efficient organic solar cells. Issue 18 (25th March 2019) - Jia, Yu; Zhang, Yun; Jiang, Wei; Su, Bin; Liu, Chunbo; Zhu, Enwei; Che, Guangbo
Abstract : The BTT-FIC-based device achieved a champion PCE of 12.65% for the benzo[1, 2- b :4, 5- b ′]di(cyclopenta[2, 1- b :3, 4- b ′]dithiophene)-containing NFAs based OSCs. Abstract : A new electron-rich central core (BTT) based on benzo[1, 2- b :4, 5- b ′]dithiophene with a thio[3, 2- b ]thiophene side chain was coupled with methyl and fluorine-modified 1, 1-dicyanomethylene-3-indanone (IC) electron-withdrawing end groups to furnish two novel non-fullerene acceptors (NFAs), namely BTT-MIC and BTT-FIC. Compared to BTT-MIC, BTT-FIC exhibits a stronger near-infrared (NIR) absorption with a smaller optical bandgap (1.47 eV). The BTT-FIC/PM6 based device achieved a champion PCE of 12.65% for benzo[1, 2- b :4, 5- b ′]di(cyclopenta[2, 1- b :3, 4- b ′]dithiophene)-containing NFA based organic solar cells (OSCs), while the BTT-FIC/PM6 based device delivered a PCE of 10.04% with a high V oc of over 1 V. Fluorinated IC is more suitable for this new core BTT than methyl substituted IC, because fluorine atoms enhance the charge transport (CT) state (absorption) and are also beneficial to exciton dissociation, charge mobility and morphology. This work revealed that BTT with a thieno[3, 2- b ]thiophene side chain is an effective electron-donating core for creating effective NFAs and fluorinated IC is a suitable end group for BTT.